La sexualité des filles et des garçons dans le Paris d’après-guerre : du Code pénal de 1810 aux lois du genre - Véronique Blanchard; Régis Revenin (Criminocorpus)
From the body of judicial archives (personal records of juvenile placed at the Observation Centers for girls of Chevilly-Larue and for boys of Savigny-sur-Orge, court files for children and teenagers and files of correctional procedure of Paris), we will demonstrate that the love and sexual practices and representations of girls and boys are both subject to social norms instilled by family, school, peers, media, but also more formal legal rules (Civil Code for “paternal correction” and “vagrancy” until 1958, for measures of “education assistance” after 1958, the Penal Code for attacks on morals, a number of which are offenses against the criminal law without victim). These social and legal norms are strongly gendered and complement each other, the law serving in practice the gender morality which assigns to each sex a specific (gendered) role. The case of young gays and lesbians will also be studied in a period when certain forms of relations between individuals of same sex, including minors, are criminally reprehensible.